Improved climate change understanding and projections for coal businesses create urgent need to initiate stronger measures toward coalbed methane in India - Udayan Singh; Ajay K. Singh (Carbon Management, 2018)
In this opinion paper, we contend that in light of recent findings and the expected future of Indian coal business, fugitive methane emissions from coal mining and handling activities may come to occupy a larger share of the national GHG inventory, and therefore methane mitigation through various approaches of coalbed methane (CBM) extraction should occupy significantly more importance in mitigating climate change. The factors in play here are the increasing global warming potential (GWP) of methane from the second to the fifth assessment reports of the IPCC, calls by researchers to shift to 20-year time frames for GWP, increasing coal production by India and the availability of coal mine methane (CMM) technology for simultaneous coal and gas production.